The Impact of Internal and External Learning on Production Ramp-UP Capability: An Investigation of High-Tech Electronic Industry - Lu, Lingyu (2012)
During the rapid evolution of high-tech industry during the recent decade, its supply chain encounter with significant challenges when dealing with the relationship between demand and supply. The high variability in both demand side and profit margin cause problems to its production pattern. High-tech electronics companies have very short life cycle and price erosion during the life cycle. When a new or a new generation product first introduced to the market, its demand may surge in a very short period and requires highly responsive supply chain to cope with it. The existing literature discussed the NPD ramp-up, learning, modularity, cycle time management, process involvement and ramp-up performance, but they ignore the interaction between them. This study will fill in the research gap by looking into the determination factors of successful ramp-up and investigate how they have relationship will firm performance.